Jerusalem through the ages: from its beginnings to the Crusades - Magness, Jodi (Oxford University Press, 2024)
"The knobbiest town in the world"--so Samuel Clemens (aka Mark Twain) described Jerusalem in The Innocents Abroad, a travelogue of his visit to the Holy Land in 1867 (Fig. 0.7). He was struck by the Old City's small size; the small white domes protruding like knobs from the flat roofs of the tightly-packed houses; the narrow, crooked, uneven stone-paved streets; the poverty and filth; and the throngs of beggars: "To see the numbers of maimed, malformed and diseased humanity that throng the holy places and obstruct the gates, one might suppose that the ancient days had come again, and that the angel of the Lord was expected to descend at any moment to stir the waters of Bethesda. Jerusalem is mournful, and dreary, and lifeless. I would not desire to live here." The nineteenth century witnessed the beginning of scientific exploration of the Holy Land, as European colonial powers sought to gain a foothold in Ottoman Palestine amid growing scientific interest in using archaeology to verify the Bible. Thousands of westerners--clerics, scholars, military men, pilgrims, adventure-seekers, and tourists--poured into the country. Twain vividly describes the overwhelming experience of sightseeing in Jerusalem: "We are surfeited with sights. Nothing has any fascination for us, now, but the Church of the Holy Sepulchre. We have been there every day, and have not grown tired of it; but we are weary of every thing else. The sights are too many. They swarm about you at every step; no single foot of ground in all Jerusalem or within its neighborhood seems to be without a stirring and important history of its own. It is a very relief to steal a walk of a hundred yards without a guide along to talk unceasingly about every stone you step upon and drag you back ages and ages to the day when it achieved celebrity. It seems hardly real when I find myself leaning for a moment on a ruined wall and looking listlessly down into the historic pool of Bethesda. I did not think such things could be so crowded together as to diminish their interest. But in serious truth, we have been drifting about, for several days, using our eyes and our ears more from a sense of duty than any higher and worthier reason. And too often we have been glad when it was time to go home and be distressed no more about illustrious localities. Our pilgrims compress too much into one day. One can gorge sights to repletion as well as sweetmeats. Since we breakfasted, this morning, we have seen enough to have furnished us food for a year's reflection if we could have seen the various objects in comfort and looked upon them deliberately."--